2014
DOI: 10.5194/amt-7-1649-2014
|View full text |Cite
|
Sign up to set email alerts
|

Clues for a standardised thermal-optical protocol for the assessment of organic and elemental carbon within ambient air particulate matter

Abstract: Along with some research networking programmes, the European Directive 2008/50/CE requires chemical speciation of fine aerosol (PM2.5), including elemental (EC) and organic carbon (OC), at a few rural sites in European countries. Meanwhile, the thermal-optical technique is considered by the European and US networking agencies and normalisation bodies as a reference method to quantify EC-OC collected on filters. Although commonly used for many years, this technique still suffers from a lack of information on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…values (by about 15 %) were measured by the low-frequency samples (Fig. 4), consistent with results from a suburban site in Europe (Chiappini et al, 2014). Although the EC measurement is not susceptible to sampling artifacts, thermaloptical determination of EC could be largely complicated by the transformation of OC into char OC (Yang and Yu, 2002).…”
Section: Effect Of Sampling Frequency On the Analytical Artifactsupporting
confidence: 87%
See 1 more Smart Citation
“…values (by about 15 %) were measured by the low-frequency samples (Fig. 4), consistent with results from a suburban site in Europe (Chiappini et al, 2014). Although the EC measurement is not susceptible to sampling artifacts, thermaloptical determination of EC could be largely complicated by the transformation of OC into char OC (Yang and Yu, 2002).…”
Section: Effect Of Sampling Frequency On the Analytical Artifactsupporting
confidence: 87%
“…A major problem in thermal-optical methods is that a substantial fraction of organic species can be transformed into materials whose thermal and optical behaviors are quite similar to EC (these materials are typically termed char OC or pyrolysis OC), thus affecting the separation of OC and EC (Yang and Yu, 2002;Chow et al, 2004;Subramanian et al, 2006). A variety of studies have shown that thermal-optical determination of OC and EC depends strongly on the analytical procedure such as the temperature protocol and the charring correction method (Chow et al, 2001(Chow et al, , 2004Schmid et al, 2001;Schauer et al, 2003;ten Brink et al, 2004;Cavalli et al, 2010;Chiappini et al, 2014;Panteliadis et al, 2015); moreover, the dependence is significantly influenced by sample properties such as source of carbonaceous components and abundance of minerals. The spatial and temporal variations of the PM 2.5 composition in China are far from being well characterized, indicating that a national PM 2.5 speciation monitoring network is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…They differ mostly in their temperature programs and optical correction types for charring based on transmittance or reflectance. The three protocols are comparable for total carbon (TC) concentrations but the results may significantly vary concerning EC-OC split [106][107][108]. Moreover, depending on the protocol used, very low EC loading can be difficult to measure, for instance in the case of samples from remote locations.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…Therefore, ACSM intercomparison workshops are regularly conducted within the framework of the European Center for Aerosol Calibration (ECAC; http://www.actris-ecac.eu, last access: 15 September 2019) at the Aerosol Chemical Monitor Calibration Center (ACMCC) in France. Data quality is ensured by determining instrumental variability between ACSMs (total mass 9 %, organics 19 %, nitrate 15 %, sulfate 28 %, ammonium 36 %; Crenn et al, 2015;Fröhlich et al, 2015a;Freney et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although intercomparison exercises provide instrumental variability, a comparison between ACSM and collocated measurements remains a fundamental aspect of in situ quality control. These intercomparisons are considered in a number of publications (e.g., Fröhlich et al, 2015b;Petit et al, 2015;Parworth et al, 2015;Ovadnevaite et al, 2014;Ripoll et al, 2015;Minguillon et al, 2015;Poulain et al, 2011b, a;Huang et al, 2018;Takegawa et al, 2009;Wang et al, 2015;Crenn et al, 2015;Guo et al, 2015;Schlag et al, 2016;Sun et al, 2015). Usually, the comparisons between ACSM and collocated measurements were only performed for a few months up to 1 year.…”
Section: Introductionmentioning
confidence: 99%